Selenium restricts cadmium uptake and improve micronutrients and proline concentration in tomato fruits - Lima, Leonardo Warzea [UNESP]; Checchio, Mirela Vantini [UNESP]; dos Reis, André Rodrigues [UNESP]; de Cássia Alves, Rita [UNESP]; Tezzoto, Tiago; Gratão, Priscila Lupino [UNESP] (Elsevier, 2019)
In order to identify the beneficial effects of Selenium (Se) in tomato (Solanum lycopersicum), genotypes MT and hp1, under Cadmium (Cd) toxicity, the following analyses were performed: Cd and Se concentration and translocation index in roots, leaves and fruits as well as the macro and micronutrients quantification, proline concentration, fruits dry weight, chlorophyll and carotenoids concentration in fruits. Se reduced the Cd concentration in roots of both genotypes. The Cd translocation to above ground parts were restricted by Se only in the MT genotype. Fruit proline concentration increased either in genotype hp1 when Se was applied alone or in the MT genotype, by the mixture of Se and Cd. When Se was applied alone the concentration of Mn and Zn in hp1 fruits and Fe in MT fruits were enhanced. The beneficial mechanisms of Se to tomato plants under Cd stress could be partially related to the restriction of Cd uptake and translocation, enhancing proline concentration and micronutrient improvements in fruits.
Keywords: Abiotic stress; Heavy metal; High pigment-1; Micro-tom; Tomato